Prosthodontics as a Specialty Private Practice: Net Income of Private Practitioners - Kent D. Nash, PhD1 and David L. Pfeifer, DDS, MS, MEd2 (Journal of Prosthodontics, 2006)
The aim of this study was to use data from a survey of prosthodontists in the US to examine average net earnings of prosthodontists in private practice.